Kids for a Happy Marriage? A Preliminary Study on Marriage Satisfaction and Presence or Absence of Children Among Married Individuals in Indonesia - Hutabarat, Alftisya Victory; Himawan, Karel Karsten (UI Scholars Hub, 2023)
Having children after marriage tends to be seen as a normative practice in Indonesia. As a result, individuals who do not have children could be at risk of experiencing a set of social stigmas. The study aims to explore whether having children is associated with one’s marital satisfaction. In particular, the present study aims to explore the differences in marital satisfaction among married individuals who have biological children, who are childfree (voluntarily childless), and who are childless (involuntarily childless). A cross-sectional survey was conducted to 210 married individuals (M age = 34.3; SD = 7.9). The result shows that child ownership is not the predominant determinant of marital satisfaction. The results of this study may pave the way and inspire further research in examining the unique psychological and social dynamics of child-free individuals, which are an understudied phenomenon in Indonesia.